THU0271 Favorable Clinical Response to Belimumab at Three Months. (23rd January 2014) - Reddy, A.; Buyon, J. P.; Franks, A. G.; Furie, R.; Kamen, D. L.; Manzi, S.; Petri, M.; Ramsey-Goldman, R.; Tseng, C.-E.; van Vollenhoven, R. F.; Wallace, D. J.; Askanase, A.
Abstract : Background: Belimumab (Benlysta) is a human monoclonal antibody that inhibits soluble B-Lymphocyte Stimulator and improves SLE disease activity. Objectives: This study was initiated to evaluate the use and efficacy of Belimumab in academic SLE clinical practices. Methods: An invitation to participate was sent to 16 physicians experienced in SLE Phase III clinical trials. All agreeing to participate completed a one page questionnaire for each patient prescribed Belimumab. Information collected included: demographics (age, gender, race/ethnicity), SLE data (duration of disease, SELENA-SLEDAI, clinical manifestation(s) targeted, background medications), and Belimumab information (start date, clinical response, side effects). Clinical response was defined as the investigator's impression of a ≥50% improvement in the initial manifestation being treated and no worsening in other organ systems. Results: Of 16 invitations sent, nine investigators accepted to participate in the study. Questionnaires on 132 treated patients were returned. The mean age was 43.7±11.0 years. 92% were female, 75.7% White, 18.3% Black, 6.1% Asian, and 4.2% Hispanic. The average SLE disease duration was 12.0±8.3 years. All except three patients were ANA positive. Concomitant medications included: antimalarials in 70.1%, immunosuppressants in 73.5% (Azathioprine 21.1%, Mycophenolate Mofetil 39.4%, Methotrexate 12.9%), and prednisone in 74.2% (average dose of 12.3±11.1, 41.7% on ≥10 mg). Only 1.5% of patients were not on any background SLE medications. Seven patients (5.3%) were on anti-malarials alone. The dominant clinical manifestation driving treatment was arthritis in 75.8% followed by rash in 49.2% and serositis in 16.7%. Other SLE manifestations included renal (9.1%), hematological (5.3%), and inability to taper steroids (5.3%). Two-thirds of patients had two or more active manifestations. Ninety patients were on Benlysta for at least 3 months. Of those, 45 (50%) patients clinically responded by 3 months with marked improvement in arthritis and/or rash. Fifty one patients were on Benlysta for at least 6 months. Of those, 22 (43.1%) patients clinically responded with improvements in arthritis, rash and/or nephritis. Data on blacks shows a similar pattern of improvement. At 3 months, 9 of 14 (64.3%) patients improved and at 6 months, 3 of 5 (60%). Of the 8 patients overall in whom Benlysta was discontinued, 2 had CNS lupus, 1 MI, 1 loss of insurance, 1 infection, 1 infusion reaction, 1 severe arthritis flare and 1 elective surgery. Conclusions: These early data support the use of Benlysta across all ethnic groups and efficacy similar to that reported in the Phase III trials. While the numbers are limited, black patients showed an improvement at 3 months. Relevant to physician and patient decision-making, improvement was observed within 3 months. Acknowledgements: This is an investigator sponsored study by GlaxoSmithKline. Disclosure of Interest: None Declared